2016
DOI: 10.12740/app/62227
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and awareness towards eating disorders among students: a preliminary study

Abstract: SummaryAims: The aim was twofold: to evaluate eating attitudes, behaviours and knowledge about eating disorders in young women and men, and to assess the relationship between measurable variables in both groups. Method:The research sample consisted of 34 females and 32 males aged 19-21. The Eating Disorders Examination Questionnaire and the Eating Disorders Awareness Test were distributed to all participants.Results: Female undergraduate students were more concerned about their weight and body shape than male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Obsessive engagement in one's appearance including the muscle structure, body weight as well as applying various diets and measures to support building muscle tissue (e.g. anabolic steroids) may predispose men to developing muscle dysmorphia (MD) (Czepczor, Brytek--Matera, 2017). It has been shown empirically that this disorder correlates with ED in men (Longobardi, Prino, Angelo, Settanni, 2017), therefore it is included in this study.…”
Section: Clinical Symptoms and Conditions Of Ed In Menmentioning
confidence: 99%
“…Obsessive engagement in one's appearance including the muscle structure, body weight as well as applying various diets and measures to support building muscle tissue (e.g. anabolic steroids) may predispose men to developing muscle dysmorphia (MD) (Czepczor, Brytek--Matera, 2017). It has been shown empirically that this disorder correlates with ED in men (Longobardi, Prino, Angelo, Settanni, 2017), therefore it is included in this study.…”
Section: Clinical Symptoms and Conditions Of Ed In Menmentioning
confidence: 99%
“…As reported by Brenana et al [ 36 ], body dissatisfaction in the group of young adults was more common and felt more strongly in women; however, men were also clearly affected in this respect. Another study [ 37 ] has also shown that women in late adolescence are more dissatisfied with their bodies compared to men. This tendency was also observed in children [ 38 ] and adolescents [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…This tendency was also observed in children [ 38 ] and adolescents [ 39 ]. Ample studies have also shown that there is both an ideal male body identified with a muscular and well-shaped figure, and an ideal female figure perceived as slim and slender [ 30 , 37 , 40 ].…”
Section: Introductionmentioning
confidence: 99%